Different expression analysis of genes between C type cytoplasmic male sterile line and its maintainer line in maize - Wang Jiyue; Wang Shengqing; Cao Moju (浙江大学学报. 农业与生命科学版)
Programmed cell death (PCD) is crucial for plant growth and development. It maintains plant normal physiologic metabolism by eliminating damaged, diseased and old cells. Numerous studies have demonstrated that cytoplasmic male sterility (CMS) in plant was associated with programmed cell death (PCD). The proper timing of PCD is very important for floral development. Based on RNA-Seq (RNA sequencing) result, we found that programmed cell death 5 gene pcd5, cytochrome oxidase gene cox1 and malate dehydrogenase gene mdh were all down-regulated in CMS-C line of maize. In this study, real-time fluorescence quantitative polymerase chain reaction (RT-qPCR) was done to further validate the expression of pcd5, cox1 and mdh genes. These analyses will contribute to better understand CMS-C mechanisms.The CMS-C line (C48-2) and its maintainer line (N48-2) were planted in the same research field of Sichuan Agricultural University. Total RNA of anther was extracted from N48-2 and C48-2 at uninucleate stages using Trizol kit. The RNA was reversely transcribed into a cDNA rst strand using PrimeScript® RT reagent kit (TaKaRa), and the genomic DNA was completely removed from total RNA before reverse transcription. The genomic DNA was extracted from leaf using cetyltrimethyl ammonium bromide (CTAB) method. To verify the expression levels of pcd5, cox1 and mdh genes, the RT-qPCR was performed using a commercial kit (AccuPower® 2X Greenstar qPCR Master Mix, Bioneer). Specific primers were designed in conserved region of coding sequence (CDS), and the 18S and β-actin were assigned as internal control genes for RT-qPCR. PCR and RT-PCR amplification of pcd5 were performed with TAR® HS DNA polymerase (TaKaRa) using specific primer. To verify the results of pyrosequencing, high resolution melting curve (HRM) was performed using a commercial kit (AccuPower® 2X Greenstar qPCR Master Mix, Bioneer). HRM primers were designed in the mutant region based on RT-qPCR. All reactions were performed in triplicate.Gene expression analysis showed that the pcd5, cox1 and mdh genes were down-regulated in C48-2 in comparison to N48-2, and the result was consistent with RNA-Seq result. The results of PCR revealed that the coding region of genomic DNA had no difference between C48-2 and N48-2. An insertion mutation was detected in C48-2 by RT-qPCR and pyrosequencing, which was also proved by HRM. As a consequence, the mutant pcd5 transcript may be associated with the down-regulated in C48-2.In conclusion, the differential expression of pcd5, cox1 and mdh genes may interfere with the programmed cell death, and the abortion of CMS-C microspores might be closely related to the cell death. The findings provide an improved sight for investigating the relationship of PCD and pollen abortion in maize